Effects of macroeconomic shocks on banking sector loan quality in Kenya - Shammah, Wema Oduor (Strathmore University, 2020)
This a paper uses two approaches to analyse the link between loan quality and macroeconomic performance. First evaluating the interaction between different macroeconomic factors using panel regressions second applying a panel vector autoregressive model in modelling the same macro-financial interactions. Using panel datafrom banks 31 banks spanning between 2001 to 2018, results show that money supply is the main macro-economic factor that influences loan quality in Kenya. Impulse response fimctions are used to how that macro-economic shocks take time reduce or increase loan quality in Kenya.
Submitted in partial fulfilment of the requirements for the Degree of Bachelor of Business Science in Finance and Applied Economics at Strathmore University